2021
DOI: 10.3390/ma14030479
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Effect of Z-Warps on the Ballistic Responses of Para-Aramid 3D Angle-Interlock Fabrics

Abstract: In order to achieve an efficient ballistic protection at a low weight, it is necessary to deeply explore the energy absorption mechanisms of ballistic fabric structures. In this paper, finite element (FE) yarn-level models of the designed three-dimensional (3D) angle-interlock (AI) woven fabrics and the laminated two-dimensional (2D) plain fabrics are established. The ballistic impact responses of fabric panels with and without the interlocking Z-warp yarns during the projectile penetration are evaluated in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…For 3D angle-interlock structural materials, the current research on bulletproof ability mainly focuses on the fabric level, as illustrated in the following studies. Yang et al [ 15 ] conducted a finite element simulation of the ballistic performance of 3D angle-interlock fabrics and 2D plain laminated fabrics, and found that the 3D angle-interlock fabric ratio capacity absorbs higher than the 2D plain laminated fabric; they also found that 3D fabrics have better surface diffusion capacity. Wei et al [ 16 ] conducted ballistic impact experiments on 3D deep-angle-interlock fabrics, which revealed the impact damage evolution, energy absorption mechanism, and stress wave distribution of 3D deep-angle-interlock fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…For 3D angle-interlock structural materials, the current research on bulletproof ability mainly focuses on the fabric level, as illustrated in the following studies. Yang et al [ 15 ] conducted a finite element simulation of the ballistic performance of 3D angle-interlock fabrics and 2D plain laminated fabrics, and found that the 3D angle-interlock fabric ratio capacity absorbs higher than the 2D plain laminated fabric; they also found that 3D fabrics have better surface diffusion capacity. Wei et al [ 16 ] conducted ballistic impact experiments on 3D deep-angle-interlock fabrics, which revealed the impact damage evolution, energy absorption mechanism, and stress wave distribution of 3D deep-angle-interlock fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…Even if, nowadays, many models and simulations have been reported, from micro [14,15], meso [13,16], to macro [17,18] scales, the tests remain the ultimate and restrictive step in adopting a certain type of individual armor, generally based on aramid fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews on ballistic protection [ 10 , 11 ] point out interesting comments on failure mechanisms and very particular solutions in combining different materials for facing very different threats. Research has involved aramid fibers with different architectures, from simple or treated woven fabrics [ 12 ] to 3D fabrics [ 13 ] and unidirectional or multiaxial non-crimp fabrics, each solution being simulated with particular model conditions and tested for a specific threat, the conclusion of the documentation conducted by the authors being that each solution has to be experimentally investigated and the failure mechanisms understood in order to offer a design with very strong statistical reliability before use in combat.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews on ballistic protection [10,11], point out interesting comments on failure mechanisms and very particular solutions in combining different materials for facing very different threats. Research have been involving aramid fibers with different architectures, from simple or treated woven fabrics [12], to 3D fabrics [13] and unidirectional or multiaxial non-crimp fabrics, each solution being simulated with particular model conditions and tested for a specific threat, the conclusion of the documentation done by the authors being that each solution has to be experimentally investigated and the failure mechanisms to be understood in order to offer a design with very strong statistical reliability before using in the combat.…”
Section: Introductionmentioning
confidence: 99%
“…Even if nowadays, there were reported many models and simulations, from micro [14,15], meso [13,16], [ to macro [17,18] scales, the tests remain the ultimate and restrictive step in adopting a certain type of individual armor, generally based on aramid fabrics.…”
Section: Introductionmentioning
confidence: 99%